A platform to reproducibly evaluate human colon permeability and damage - Elizabeth E. Marr; Thomas J. Mulhern; Michaela Welch; Philip Keegan; Celia Caballero-Franco; Bryce G. Johnson; Marion Kasaian; Hesham Azizgolshani; Timothy Petrie; Joseph Charest; Elizabeth Wiellette (Scientific Reports, 2023)
Abstract The intestinal epithelium comprises diverse cell types and executes many specialized functions as the primary interface between luminal contents and internal organs. A key function provided by the epithelium is maintenance of a barrier that protects the individual from pathogens, irritating luminal contents, and the microbiota. Disruption of this barrier can lead to inflammatory disease within the intestinal mucosa, and, in more severe cases, to sepsis. Animal models to study intestinal permeability are costly and not entirely predictive of human biology. Here we present a model of human colon barrier function that integrates primary human colon stem cells into Draper’s PREDICT96 microfluidic organ-on-chip platform to yield a high-throughput system appropriate to predict damage and healing of the human colon epithelial barrier. We have demonstrated pharmacologically induced barrier damage measured by both a high throughput molecular permeability assay and transepithelial resistance. Using these assays, we developed an Inflammatory Bowel Disease-relevant model through cytokine induced damage that can support studies of disease mechanisms and putative therapeutics.